STUDI KELAYAKAN BISNIS PADA USAHA KOS - Nugraha, Rifat Tri; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to conduct a feasibility study on the Alamanda girls' boarding house business. Girls' boarding houses are a popular form of accommodation sought after by students and professionals in need of temporary living arrangements. The study evaluates various aspects of business feasibility, including market analysis, financial analysis, risk analysis, and environmental analysis. The research methodology involves collecting primary data through direct observation at the business location and conducting interviews with the business owner, staff, and customers. Secondary data is also utilized to support the analysis. The findings indicate that the Alamanda girls' boarding house business has a promising market potential. There is a high demand for girls' boarding house accommodation, particularly in areas near universities and office complexes. The financial analysis reveals a favorable long-term profit potential for the business. Based on the research findings, it can be concluded that the Alamanda girls' boarding house business is feasible for development. To enhance business success, it is recommended to implement effective marketing strategies, maintain service quality and facilities, and manage risks effectively.